Adaptations to isolated shoulder fatigue during simulated repetitive work. Part II: Recovery. (August 2016) - McDonald, Alison C.; Tse, Calvin T.F.; Keir, Peter J.
Abstract: The shoulder allows kinematic and muscular changes to facilitate continued task performance during prolonged repetitive work. The purpose of this work was to examine changes during simulated repetitive work in response to a fatigue protocol. Participants performed 20 one-minute work cycles comprised of 4 shoulder centric tasks, a fatigue protocol, followed by 60 additional cycles. The fatigue protocol targeted the anterior deltoid and cycled between static and dynamic actions. EMG was collected from 14 upper extremity and back muscles and three-dimensional motion was captured during each work cycle. Participants completed post-fatigue work despite EMG manifestations of muscle fatigue, reduced flexion strength (by 28%), and increased perceived exertion (∼3 times). Throughout the post-fatigue work cycles, participants maintained performance via kinematic and muscular adaptations, such as reduced glenohumeral flexion and scapular rotation which were task specific and varied throughout the hour of simulated work. By the end of 60 post-fatigue work cycles, signs of fatigue persisted in the anterior deltoid and developed in the middle deltoid, yet perceived exertion and strength returned to pre-fatigue levels. Recovery from fatigue elicits changes in muscle activity and movement patterns that may not be perceived by the worker which has important implications for injury risk.